1998
DOI: 10.1002/(sici)1521-4141(199806)28:06<2017::aid-immu2017>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofin vitroimmunoglobulin production by IL-12 in murine chronic graft-vs. -host disease: synergism with IL-18

Abstract: We investigated the effects of IL-12 on immunoglobulin (Ig) production in vitro in murine chronic graft-vs.-host disease (cGVHD), a lupus-like model of overt B cell activation induced by allogeneic stimulation. Addition of IL-12 to cGVHD splenocytes strongly inhibited total Ig (Ig O ), IgM and IgG1 production. Although IL-12 down-regulated IL-4, IL-5, IL-9 and IL-10 production, its inhibitory activity on Ig production could not be ascribed to down-regulation of these cytokines, as addition of saturating doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…A similar increase in Ag-induced IL-4 production in vivo may account for the increased serum IgE, as IL-4 is a known inducer of IgE class switching (30). IL-18 in combination with IL-12 has been shown to suppress the production of IgE in activated B cells (31), and IL-18 alone was reported to have no effect on IgE production in purified splenic B cells (32). Thus, in the present study, it seems probable that the increased serum IgE was mediated by increased IL-4 production from Th2 cells, and not direct B cell activation by IL-18.…”
Section: Discussionmentioning
confidence: 52%
“…A similar increase in Ag-induced IL-4 production in vivo may account for the increased serum IgE, as IL-4 is a known inducer of IgE class switching (30). IL-18 in combination with IL-12 has been shown to suppress the production of IgE in activated B cells (31), and IL-18 alone was reported to have no effect on IgE production in purified splenic B cells (32). Thus, in the present study, it seems probable that the increased serum IgE was mediated by increased IL-4 production from Th2 cells, and not direct B cell activation by IL-18.…”
Section: Discussionmentioning
confidence: 52%
“…In vitro studies have demonstrated that the combination of IL-12 and IL-18 suppress IgG1 and enhance IgG2a levels (38). However, studies of murine graft-vs-host disease suggest that IL-18 lacks this discriminatory effect and, in fact, suppresses total Ig, IgG1, and IgG2a levels in vitro (39). While IL-18 would be expected to induce IgG2a production in vivo (given its role in inducing IFN-␥), there were no significant changes in Ag-specific total Ig, IgG1, or IgG2a titers when IL-18 was administered to IL-12 ϩ/ϩ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Given the striking synergy between IL-12 and IL-18 for IFN-␥ induction (23) and given the inhibitory effects of IFN-␥ on Ig production in certain experimental systems (24,25), we evaluated whether the inhibitory effects exerted by IL-12/IL-18-derived NK cells on Ig production and cell survival were mediated by IFN-␥. As indicated in Fig.…”
Section: Distinct Effects Of Nk/t-nk Cells On Ig Production By Syngenmentioning
confidence: 99%